Estudo da bioacessibilidade e biodisponibilidade de pigmentos microalgais - Pinheiro, Pricila Nass (2024)
Microalgal biomass is acknowledged as a promising source of bioactive compounds, with carotenoids and chlorophylls being particularly highlighted. These compounds possess intriguing attributes for maintaining health. However, for them to assume a protagonist role in biological functions, they must be bioaccessible for intestinal uptake and subsequent systemic distribution. There is a growing concern regarding the influence of the microalgal matrix on the bioaccessibility and bioavailability of these bioactive structures. Therefore, comprehending the stages that limit their bioavailability is imperative for formulating functional foods/ingredients. To this end, various strategies involving microalgal ingredients/products (whole dry biomass [WDB], whole ultrasonicated paste [WUP], and liposoluble pigment emulsion [LPE]) were employed in in vitro digestion, aiming to enhance the bioaccessibility and absorption by Caco-2 cells of carotenoids and chlorophylls from two commercial species of microalgae, Chlorella vulgaris and Arthrospira platensis. Consequently, the bioaccessibility and cellular absorption of carotenoids and chlorophylls increased according to the matrix (LPE > WUP > WDB). These findings resulted in 2 articles and 1 book chapter (published or in the publication process), which have been structured into chapters in this document. Chapters 1 and 2 correspond to the articles titled "Bioaccessibility and bioavailability of bioactive compounds from microalgae" (article under review for publication) and "Guidance for formulating ingredients/products from Chlorella vulgaris and Arthrospira platensis considering carotenoid and chlorophyll bioaccessibility and cellular uptake" (research article/publication completed). Chapter 3 is associated with a contribution in a book and is titled "Food Bioactive Compounds from Microalgae" (book chapter already published). Finally, it is essential to emphasize that the evaluation of bioaccessibility and bioavailability revealed that the nature of the product exerts a substantial influence on the carotenoids and chlorophylls present in microalgae, which can play a crucial role in formulating foods and functional products using ingredients derived from microalgae. These results underscore the importance of considering the final product formulations to optimize the delivery and effectiveness of these bioactive compounds.